Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Stoichiometric engineering of aza-Michael chemistry for controlled foam generation - Vipin G. Krishnan; Baptiste Clement; Antoine Duval; Leandro Jacomine; Léa Skorlic; Rémi Perrin; Alexandru Sarbu; Wiebke Drenckhan-Andreatta (Chemical Engineering Journal, 2026)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Climate change vulnerability of Arctic char across Scandinavia - Clint C. Muhlfeld; Timothy J. Cline; Anders G. Finstad; Dag O. Hessen; Sam Perrin; Jens Thaulow; Diane Whited; Leif Asbjørn Vøllestad (Global Change Biology, 2024)
Climate change is anticipated to cause species to shift their ranges upward and poleward, yet space for tracking suitable habitat conditions may be limited for range‐restricted species at the highest elevations and latitudes of the globe. Consequently, range‐restricted species inhabiting Arctic freshwater ecosystems, where global warming is most pronounced, face the challenge of coping with changing abiotic and biotic conditions or risk extinction. Here, we use an extensive fish community and environmental dataset for 1762 lakes sampled across Scandinavia (mid‐1990s) to evaluate the climate vulnerability of Arctic char ( Salvelinus alpinus ), the world's most cold‐adapted and northernly distributed freshwater fish. Machine learning models show that abiotic and biotic factors strongly predict the occurrence of Arctic char across the region with an overall accuracy of 89 percent. Arctic char is less likely to occur in lakes with warm summer temperatures, high dissolved organic carbon levels (i.e., browning), and presence of northern pike ( Esox lucius ). Importantly, climate warming impacts are moderated by habitat (i.e., lake area) and amplified by the presence of competitors and/or predators (i.e., northern pike). Climate warming projections under the RCP8.5 emission scenario indicate that 81% of extant populations are at high risk of extirpation by 2080. Highly vulnerable populations occur across their range, particularly near the southern range limit and at lower elevations, with potential refugia found in some mountainous and coastal regions. Our findings highlight that range shifts may give way to range contractions for this cold‐water specialist, indicating the need for pro‐active conservation and mitigation efforts to avoid the loss of Arctic freshwater biodiversity.

Possibly seismically triggered avalanches after the S1222a Marsquake and S1000a impact event - A. Lucas; I.J. Daubar; M. Le Teuff; C. Perrin; T. Kawamura; L. Posiolova; P. Lognonné; S. Rodriguez; D. Giardini; G. Sainton; A. Mangeney; A. McEwen (Icarus, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Structure-based optimization of aminothiadiazole inhibitors of AKT - Deborah S. Mortensen; Sayee G. Hegde; Sophie M. Perrin-Ninkovic; Sogole Bahmanyar; Meg McCarrick; Roy Harris; Robert Hilgraf; Branden G. S. Lee; Jeff McKie; Lisa Nadolny; John Sapienza; Alice Collette; et al. (Medicinal Chemistry Research, 2023)

Effects of a multifaceted intervention to promote the use of intravenous iron sucrose complex instead of ferric carboxymaltose in patients admitted for more than 24 h - Justine Touchard; G. Perrin; S. Berdot; J. Pouchot; M. C. Loustalot; B. Sabatier (European Journal of Clinical Pharmacology, 2021)

If you plant it, they will come: quantifying attractiveness of exotic plants for winter-active flower visitors in community gardens - Perrin Tasker; Chris Reid; Andrew D. Young; Caragh G. Threlfall; Tanya Latty (Urban Ecosystems, 2020)

Are glacial refugia hotspots of speciation and cytonuclear discordances? Answers from the genomic phylogeography of Spanish common frogs - Christophe Dufresnes; Alfredo G. Nicieza; Spartak N. Litvinchuk; Nicolas Rodrigues; Daniel L. Jeffries; Miguel Vences; Nicolas Perrin; Íñigo Martínez‐Solano (Molecular Ecology, 2020)
Subdivided Pleistocene glacial refugia, best known as “refugia within refugia”, provided opportunities for diverging populations to evolve into incipient species and/or to hybridize and merge following range shifts tracking the climatic fluctuations, potentially promoting extensive cytonuclear discordances and “ghost” mtDNA lineages. Here, we tested which of these opposing evolutionary outcomes prevails in northern Iberian areas hosting multiple historical refugia of common frogs ( Rana cf. temporaria ), based on a genomic phylogeography approach (mtDNA barcoding and RAD‐sequencing). We found evidence for both incipient speciation events and massive cytonuclear discordances. On the one hand, populations from northwestern Spain (Galicia and Asturias, assigned to the regional endemic R. parvipalmata ), are deeply‐diverged at mitochondrial and nuclear genomes (~4 My of independent evolution), and barely admix with northeastern populations (assigned to R. temporaria sensu stricto) across a narrow hybrid zone (~25 km) located in the Cantabrian Mountains, suggesting that they represent distinct species. On the other hand, the most divergent mtDNA clade, widespread in Cantabria and the Basque country, shares its nuclear genome with other R. temporaria s. s. lineages. Patterns of population expansions and isolation‐by‐distance among these populations are consistent with past mitochondrial capture and/or drift in generating and maintaining this ghost mitochondrial lineage. This remarkable case study emphasizes the complex evolutionary history that shaped the present genetic diversity of refugial populations, and stresses the need to revisit their phylogeography by genomic approaches, in order to make informed taxonomic inferences.

Alan Noel Baker 1940–2017 - Koen van Waerebeek; Anton van Helden; Bernd Würsig; Robert L. Brownell; Frank Cipriano; William F. Perrin; James G. Mead (Marine Mammal Science, 2018)

Investigation of recharge dynamics and flow paths in a fractured crystalline aquifer in semi-arid India using borehole logs: implications for managed aquifer recharge - M. Alazard; A. Boisson; J-C. Maréchal; J. Perrin; B. Dewandel; T. Schwarz; M. Pettenati; G. Picot-Colbeaux; W. Kloppman; S. Ahmed (Hydrogeology Journal, 2016)

Hydrology under change: an evaluation protocol to investigate how hydrological models deal with changing catchments - G. Thirel; V. Andréassian; C. Perrin; J.-N. Audouy; L. Berthet; P. Edwards; N. Folton; C. Furusho; A. Kuentz; J. Lerat; G. Lindström; E. Martin; et al. (Hydrological Sciences Journal, 2015)

Resurrection of Mesoplodon hotaula Deraniyagala 1963: A new species of beaked whale in the tropical Indo‐Pacific - Merel L. Dalebout; C. Scott Baker; Debbie Steel; Kirsten Thompson; Kelly M. Robertson; Susan J. Chivers; William F. Perrin; Manori Goonatilake; R. Charles Anderson; James G. Mead; Charles W. Potter; Lisa Thompson; et al. (Marine Mammal Science, 2014)
We present genetic and morphological evidence supporting the recognition of a previously synonymized species of Mesoplodon beaked whale in the tropical Indo‐Pacific, Mesoplodon hotaula . Although the new species is closely‐related to the rare ginkgo‐toothed beaked whale M. ginkgodens, we show that these two lineages can be differentiated by maternally (mitochondrial DNA ), biparentally (autosomal), and paternally (Y chromosome) inherited DNA sequences, as well as by morphological features. The reciprocal monophyly of the mt DNA genealogies and the largely parapatric distribution of these lineages is consistent with reproductive isolation. The new lineage is currently known from at least seven specimens: Sri Lanka (1), Gilbert Islands, Republic of Kiribati (1+), Palmyra Atoll, Northern Line Islands, U.S.A. (3), Maldives (1), and Seychelles (1). The type specimen (Sri Lanka) was described as a new species, M. hotaula , in 1963, but later synonymized with M. ginkgodens . This discovery brings the total number of Mesoplodon species to 15, making it, by far, the most speciose yet least known genus of cetaceans.

Climate‐driven range shifts explain the distribution of extant gene pools and predict future loss of unique lineages in a marine brown alga - J. Assis; E. A. Serrão; B. Claro; C. Perrin; G. A. Pearson (Molecular Ecology, 2014)
The climate‐driven dynamics of species ranges is a critical research question in evolutionary ecology. We ask whether present intraspecific diversity is determined by the imprint of past climate. This is an ongoing debate requiring interdisciplinary examination of population genetic pools and persistence patterns across global ranges. Previously, contrasting inferences and predictions have resulted from distinct genomic coverage and/or geographical information. We aim to describe and explain the causes of geographical contrasts in genetic diversity and their consequences for the future baseline of the global genetic pool, by comparing present geographical distribution of genetic diversity and differentiation with predictive species distribution modelling ( SDM ) during past extremes, present time and future climate scenarios for a brown alga, F ucus vesiculosus . SDM showed that both atmospheric and oceanic variables shape the global distribution of intertidal species, revealing regions of persistence, extinction and expansion during glacial and postglacial periods. These explained the distribution and structure of present genetic diversity, consisting of differentiated genetic pools with maximal diversity in areas of long‐term persistence. Most of the present species range comprises postglacial expansion zones and, in contrast to highly dispersive marine organisms, expansions involved only local fronts, leaving distinct genetic pools at rear edges. Besides unravelling a complex phylogeographical history and showing congruence between genetic diversity and persistent distribution zones, supporting the hypothesis of niche conservatism, range shifts and loss of unique genetic diversity at the rear edge were predicted for future climate scenarios, impoverishing the global gene pool.

Effects of shade on growth, biomass allocation and leaf morphology in European yew (Taxus baccata L.) - Philip M. Perrin; Fraser J. G. Mitchell (European Journal of Forest Research, 2013)

The allometry of parrot BMR: seasonal data for the Greater Vasa Parrot, Coracopsis vasa, from Madagascar - Barry G. Lovegrove; Mike R. Perrin; Mark Brown (Journal of Comparative Physiology B, 2011)

Population genetic structure of the endangered Eastern Bristlebird, Dasyornis brachypterus; implications for conservation - David G. Roberts; Jack Baker; Cécile Perrin (Conservation Genetics, 2011)

Ten polymorphic microsatellite markers for the endangered Australian Eastern Bristlebird, Dasyornis brachypterus - C. Perrin; D. G. Roberts (Conservation Genetics Resources, 2010)

Reasoning as simulation - Nicholas L. Cassimatis; Arthi Murugesan; Perrin G. Bignoli (Cognitive Processing, 2009)

A DIVERGENT mtDNA LINEAGE AMONG MESOPLODON BEAKED WHALES: MOLECULAR EVIDENCE FOR A NEW SPECIES IN THE TROPICAL PACIFIC? - Merel L. Dalebout; C. Scott Baker; Debbie Steel; Kelly M. Robertson; Susan J. Chivers; William F. Perrin; James G. Mead; Roger V. Grace; T. David Schofield (Marine Mammal Science, 2007)

CRANIAL DESCRIPTION AND GENETIC IDENTITY OF THE HOLOTYPE SPECIMEN OF TURSIOPS ADUNCUS (EHRENBERG, 1832) - William F. Perrin; Kelly M. Robertson; Peter J. H. Van Bree; James G. Mead (Marine Mammal Science, 2007)
Two species of bottlenose dolphins are currently recognized by most cetologists: the pan‐tropical and temperate Tursiops truncatus and the endemic Indo‐Pacific T. aduncus. The latter was described from a specimen from the Red Sea, with nothing in the description that would allow referral of the specimen to one or the other of the two species. Because both species occur in the northern Indian Ocean, it was possible that the holotype specimen was actually a common bottlenose dolphin, not of the Indo‐Pacific species. The holotype skull was thought lost but has been found in the Berlin Museum. We describe the skull and examine its affinities through comparison of a partial mtDNA control‐region sequence with sequences from South Africa and through application of classification functions from a discriminant analysis of the two putative species from Taiwan. The mtDNA sequence is identical to that of South African specimens referred to the Indo‐Pacific species, and the multivariate likelihood assignment associates the skull with Taiwanese specimens referred to that species. These results ensure the correctness of use of the name T. aduncus for the species.

GENETIC ANALYSIS OF KILLER WHALE ( ORCINUS ORCA ) HISTORICAL BONE AND TOOTH SAMPLES TO IDENTIFY WESTERN U.S. ECOTYPES - Phillip A. Morin; Richard G. LeDuc; Kelly M. Robertson; Nicole M. Hedrick; William F. Perrin; Michael Etnier; Paul Wade; Barbara L. Taylor (Marine Mammal Science, 2006)
Little is known about the historical range of killer whale ecotypes in the eastern North Pacific (ENP). It is possible that ranges have shifted in the last few decades because of changes in availability of food. In particular, the southern resident ecotype, currently found primarily in the inland waters of Washington State, is known to prey extensively on salmon, which have declined in recent decades along the outer coasts of Washington, Oregon, and California. To investigate historical distributions of this and the other ENP ecotypes, samples of teeth and bones were obtained from NMFS and museum collections. We amplified a short section of the mitochondrial DNA control region that contains four diagnostic sites that differentiate between haplotypes found in ecotypes of ENP killer whales. Results did not show any southern resident haplotypes in samples from south of the Washington State inland waterways. One whale genetically identified as a northern resident extends the known southernmost distribution of the population from Oregon to California. Items of diet identified from stomach contents of six of the whales genetically identified to ecotype conformed with what is known of the feeding habits of the various ecotypes.

Arsenic in groundwater of the Bengal Basin, Bangladesh: Distribution, field relations, and hydrogeological setting - Peter Ravenscroft; William G. Burgess; Kazi Matin Ahmed; Melanie Burren; Jerome Perrin (Hydrogeology Journal, 2005)

Molecular Line Parameters for the “MASTER” (Millimeter Wave Acquisitions for Stratosphere/Troposphere Exchange Research) Database - A. Perrin; C. Puzzarini; J.-M. Colmont; C. Verdes; G. Wlodarczak; G. Cazzoli; S. Buehler; J.-M. Flaud; J. Demaison (Journal of Atmospheric Chemistry, 2005)

Relationships of job, age, and life conditions with the causes and severity of occupational injuries in construction workers - Nearkasen Chau; Grome C. Gauchard; Christian Siegfried; Lahoucine Benamghar; Jean-Louis Dangelzer; Martine Franais; Rgis Jacquin; Alain Sourdot; Philippe P. Perrin; Jean-Marie Mur (International Archives of Occupational and Environmental Health, 2004)

Daily torpor in elephant shrews (Macroscelidea: Elephantulus spp.) in response to food deprivation - B. G. Lovegrove; J. Raman; M. R. Perrin (Journal of Comparative Physiology B, 2001)

Heterothermy in elephant shrews, Elephantulus spp. (Macroscelidea): daily torpor or hibernation? - B. G. Lovegrove; J. Raman; M. R. Perrin (Journal of Comparative Physiology B, 2001)

Monsoonal influences on a mesoscale convective systemover midlatitude South Australia - G. M. Perrin; C. J. C. Reason (Meteorology and Atmospheric Physics, 2000)

PHYLOGENETIC RELATIONSHIPS AMONG THE DELPHINID CETACEANS BASED ON FULL CYTOCHROME B SEQUENCES - R. G. Leduc; W. F. Perrin; A. E. Dizon (Marine Mammal Science, 1999)
A bstract Complete cytochrome b gene sequences from all but one species of delphinid plus four outgroups were analyzed using parsimony, maximum likelihood, and neighbor‐joining methods. The results indicate the need for systematic revision of the family; a provisional classification is presented and compared to previous studies. Among the suggested revisions are removal of Orcinus from the Globicephalinae, placement of Grampus within the Globicephalinae, removal of all Lagenorhynchus spp. from the Delphininae, and placement of Sousa in the Delphininae. The genus Lagenorhynchus is found to be polyphyletic. L. albirostris (type species for the genus) and L. acutus are not closely related to each other or to nominal congeners. L. acutus is therefore assigned to the genus Leucopleurus . The remaining four Lagenorhynchus species are closely related to Lissodelphis and Cephalorbynchus and are placed in the genus Sagmatias . These three genera constitute the revised Lissodelphininae. Within the Delphininae, a well‐supported clade includes the two species of Delphinus, Stenella clymene, S. frontalis, S. coeruleoalba , and the aduncus form of Tursiops truncatus . Accepting the monophyly of this group renders the genera Stenella and Tursiops polyphyletic. Apart from this finding, phylogenetic resolution within the Delphininae was poor, so comprehensive taxonomic revision of this group awaits further study.

Ectomycorrhizal associations with Cedrus atlantica (Endl) Manetti ex Carrière. I. Mycorrhizal synthesis with Tricholoma tridentinum Singer var. cedretorum Bon - H. Nezzar-Hocine; R. Perrin; R. Halli-Hargas; G. Chevalier (Mycorrhiza, 1998)

The effects of increasing CO 2 and temperature on oak leaf palatability and the implications for herbivorous insects - S. J. Dury; J. E. G. Good; C. M. Perrins; A. Buse; T. Kaye (Global Change Biology, 1998)
Rising levels of atmospheric CO 2 are expected to perturb forest ecosystems, although the extent to which specific ecological interactions will be modified is unclear. This research evaluates the effects of elevated CO 2 and temperature, alone and in combination, on the leaf nutritional quality of Pendunculate oak ( Quercus robur L. ), and the implications for herbiverous insect defoliators are discussed. A 3 °C temperature rise reduced leaf nutritional quality, by reducing foliar nitrogen concentration and increasing condensed tannin content. Doubling atmospheric CO 2 temporarily increased total phenolics, but also reduced leaf toughness. The nutritional quality of the second leaf flush (lammas growth) was considerably reduced at elevated CO 2 . It is concluded that larval development of spring‐feeding defoliators and hence adult fecundity may be adversely affected by increased temperatures.

STENELLA ATTENUATA FROM CURAÇAO MISIDENTIFIED AS S. COERULEOALBA - RICHARD G. LEDUC; WILLIAM F. PERRIN; ADOLPHE O. De BROT; NÉLIO B. BARROS; PETER J. H. VAN BREE (Marine Mammal Science, 1997)